Efficacy and Adverse Events of Vaccines against SARS CoV-2, authorized in the years 2020 and 2021 - Sandoval Olaya, Paul (2023)
The objective of the article is to analyze, summarize and present the best scientific evidence that demonstrates the efficacy and adverse events of vaccines against SARS CoV-2 authorized in the years 2020 and 2021, whose method used was based on the search mainly in the bases of data from: PudMed, CDC, EBSCO, Dynamed, and Google Scholar, on the research published in these years, without language restrictions, prioritizing English and using the terms "vaccine", "SARS-CoV-2", "Efficacy" "Safety" "Side Effects", including all studies that determine the efficacy and adverse events of these vaccines and excluding those that analyze allergies, anaphylaxis. The results obtained after collecting, classifying and filtering the investigations that determine the efficacy and adverse events of COVID-19 vaccines, it is concluded that the vaccines licensed and used against SARS-CoV-2 are effective in reducing the severity of the disease with minimal adverse events.